Neuron-astrocyte interaction enhance GABAergic synaptic transmission in a manner dependent on key metabolic enzymes - Kaczor, Przemysław; Rakus, Dariusz; Mozrzymas, Jerzy W. (Frontiers in Cellular Neuroscience, 2015)
GABA is the major inhibitory neurotransmitter in the adult brain and mechanisms of GABAergic inhibition have been intensely investigated in the past decades. Recent studies provided evidence for an important role of astrocytes in shaping GABAergic currents. One of the most obvious, but yet poorly understood, mechanisms of the cross-talk between GABAergic currents and astrocytes is metabolism including neurotransmitter homeostasis. In particular, how modulation of GABAergic currents by astrocytes depends on key enzymes involved in cellular metabolism remains largely unknown. To address this issue, we have considered two simple models of neuronal cultures: nominally astrocyte-free neuronal culture (NC) and neuronal-astrocytic co-cultures (ANCC) and miniature Inhibitory Postsynaptic Currents (mIPSCs) were recorded in control conditions and in the presence of respective enzyme blockers. We report that enrichment of neuronal culture with astrocytes results in a marked increase in mIPSC frequency. This enhancement of GABAergic activity was accompanied by increased number of GAD65 and vGAT puncta, indicating that at least a part of the frequency enhancement was due to increased number of synaptic contacts. Inhibition of glutamine synthetase (with MSO) strongly reduced mIPSC frequency in ANCC but had no effect in NC. Moreover, treatment of ANCC with inhibitor of glycogen phosphorylase (BAYU6751) or with selective inhibitor of astrocytic Krebs cycle,fluoroacetate, resulted in a marked reduction of mIPSC frequency in ANCC having no effect in NC. We conclude that GABAergic synaptic transmission strongly depends on neuron-astrocyte interaction in a manner dependent on key metabolic enzymes as well as on the Krebs cycle.